Simulator-Based and Hands-On Methods for Marine Engineering: A Descriptive and Comparative Analysis - Singuit, Dominic Rey Y.; Villalas, Betaliano S.; Aranzado, Rey Q. (Asian Journal of Science and Applied Technology, 2023)
This study assessed the simulator-based and hands-on methods of selected third-year marine engineering students at the University of Cebu Lapulapu and Mandaue. This study determined the respondents’ age, gender, and grade point average profile. Furthermore, it defined the subjects’ performance levels and the difference between simulator-based and hands-on methods in Propulsion Ancillary System and Gas Turbine (PASGT). This study used the descriptive-comparative method. The researchers used a convenient number as subjects of the total number of enrollees in the course. The investigation was carried out by the researchers in University of Cebu-Lapulapu and Mandaue. The study used a scenario-based researcher-made assessment tool to gather the data needed. The researchers used frequency count, percent, mode, and weighted to treat the data. The study revealed that in the simulator-based method, the subject’s performance in the chosen competencies of the course PASGT obtained a much higher mean interpreted as very satisfactory. It also established a significant difference between the subject’s performance in the simulator-based and the hands-on methods. The findings concluded that the simulation-based methods in teaching and learning the PASGT course have substantial educational effects. With particular consideration to the students’ psychomotor domain, the medium provides learning in a manner that is very suitable to the current practices of the younger generation.